La relación subsidiaria y complementaria entre los sistemas nacionales de protección de derechos humanos y el sistema interamericano - Lengua Parra, Adrián (Pontificia Universidad Católica del Perú, 2017)
The author presents us the increasing force of the partnership between International Law and its entities by one side and the National States by the other, without impairing with its Sovereignty; and also how this process has created a surveillance and supervision praxis, focused on the possibility that State activities may affect the rights of its citizens.This article includes as well a survey on the theory and legal precedents that are most noteworthy, pointing to comprehend the passing from a subsidiary vision of the international legal order towards the national to one that is complementary, without prejudice to unpolished or unfinished aspects of the agenda. Everything in order to the full effect of Human Rights.

El autor nos presenta la vigencia de la relación del Derecho internacional y sus organismos con los Estados, sin mellar su soberanía y como este proceso ya ha ido creando una práctica de controles y supervisión de las actividades estatales que pudieran ser nocivas para los derechos de sus ciudadanos.Incluye, además, un análisis de la doctrina y la jurisprudencia más relevante a fin de comprender el paso de una visión subsidiaria del ordenamiento internacional para con el nacional a un enfoque complementario, en el que hay todavía aspectos que pulir y depurar con el fin de la plena vigencia de los derechos humanos.
The subsidiary and complementary relationship between the national systems of protection of human rights and the inter-american system
Keywords: Derechos humanos; Jurisprudencia nacional del internacional; Subsidiariedad; Sistema interamericano de derechos humanos; Complementariedad; https://purl.org/pe-repo/ocde/ford#5.05.01